(untitled) (Journal of Oriental Studies, 2016)
This article highlights the features of the application of zoonyms in Chinese, Kazakh, Russian and English languages. Since the dog is one of the oldest domestic animals, it has been very close to human house, its habits and appearance have been used as a metaphor for characterizing human reality. In these four cultures zoonym «dog» is used in negative and positive ways, but, nevertheless, negatory connotation is more common. On an example of a component – idiom with zoonym «dog» describes the features of linguocultural differences of these languages, and the use of zoonyms in intercultural communication.